AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN SALAM - Nunung Hasanan (Universitas Pekalongan, 2015)
Background: One cause damage to cells-cells in the body that can cause disease are free radicals. Free radicals can come from outside the body or from the body. Ocsigen free radicals or reactive species (ROS) found in the body can be inhibited by antioxidants. Bay leaves are natural ingredients that contain antioxidants because it contains flavonoids. The purpose of this study is to look at the content of leaves as a natural antioxidant Method The research method by laboratory tests both quantitatively and qualitatively Result: Extraction of bay leaves (Syzygium polyanthum) by maceration using 70% ethanol as a solvent. Testing Qualitative (phytochemical test) showed the presence of flavonoids in extracts of leaves, and the quantitative assay with DPPH ethanol extract of leaves that is IC50 = 89 627, the concentration of antioxidant compounds contained in the leaves have antioxidant effects greater than vitamin C to decrease characters radical. Keywords: antioxidants, bay leaves, DPPH.